Silício como atenuador do estresse hídrico em feijão-caupi por meio do mecanismo antioxidante e desempenho agronômico - Araújo, Edilene Daniel de (2017)
Cowpea (Vigna unguiculata (L.) Walp.) is one of the most important food crops in the Northeastern semi-arid region for its high nutritional value. However, in the Northeast region, water scarcity is one of the factors that reduce its yield, with various consequences for its development and yield. This study aimed to evaluate the application of silicon (Si) as inductor of tolerance to water restriction in cowpea genotypes. The experiment consisted of a 5 x 2 x 3 factorial scheme, corresponding to five cowpea genotypes (‘BRS Marataoã’, ‘BR 17 Gurgueia’, ‘BRS Rouxinol’, ‘Paulistinha’ and ‘Costela de Vaca’) subjected to two water conditions (E 0- without water deficit/W-100% of field capacity and E1- with water deficit/W-50% of field capacity) and three Si doses (0; 49 and 70 mg L^-1 of Si), resulting in 30 treatments, arranged in randomized blocks, with five replicates. Agronomic (growth and production), physiological (leaf water potential and relative water content) and biochemical (superoxide dismutase, catalase, ascorbate peroxidase, free proline, total soluble proteins and total soluble carbohydrates) evaluations were performed. The obtained data were subjected to univariate and multivariate analyses, using the software Statistica 7.0. The evaluated genotypes showed increase in growth and development, when cultivated under water limitation of 50% of available water and treated with Si. Si reduced the leakage of electrolytes in ‘Paulistinha’ and ‘BRS Marataoã’. The antioxidant activity of the enzymes SOD, CAT and APX were potentiated by Si leaf application. The genotypes ‘BRS Marataoã’ withstood the water restriction better through the application of Si.